Provision of Food for the Population of Polish Urban Agglomerations during the War of 1939. Plans and their Implementation on the Example of Warsaw - Grzegorz JASIŃSKI (Bulletin of "Carol I" National Defense University)
The subject of battlefield logistics security in some countries lies outside the mainstream of military historians’ studies of armed conflicts in the broadest sense. This is surprising insofar as these activities almost always determine the manner and possibilities of conducting military operations. For example, this issue can be seen in the Polish literature on the defensive war of 1939. Although several comprehensive studies have been written, significant gaps remain in many areas, hindering a proper understanding of various aspects of the September 1939 fighting. One such topic is the preparation of the Polish civilian and military administration to meet the food needs of the civilian population in urban agglomerations in September 1939. The purpose of this article is to show the inadequacies of Polish preparations against the background of German efforts in this regard and to determine what effect victualling had on the ability to conduct a prolonged and organized defense. For this purpose, the author will use the example of one of the longest-defending urban centers in September 1939, namely the Polish capital, Warsaw.